TURKISH CULTURE AND NATIONAL TRADITIONS - Akhmedova Nozimakhon (Journal of new century innovations, 2024)
Abstract: Turkish culture combines a very diverse and heterogeneous set of elements originating from different cultures of Eastern European, Eastern Mediterranean, Caucasian, Middle Eastern and Central Asian traditions. Many of these traditions were originally consolidated by the Ottoman Empire, a multi-ethnic and multi-religious state that spanned Southern Europe, Eastern Europe, the Middle East, and North Africa. This article talks about the culture and national traditions of the Turkish people.